Empowerment and intentions to resist future change: the moderating effect organization-based self-esteem - Pires, Daniela Filipa Pinto (2017)
Nowadays, organizations face a constant need for adaptability, increasing the importance of change management. Our study focuses of how empowering leadership influences intentions to resist future changes, mediated by the effects of psychological and structural empowerment. From the responses of the two questionnaires (N1=230; Ntf=113), we found that empowering leadership fosters psychological and structural empowerment. Structural empowerment was the main driver in reducing intentions to resist future change when an employee has high organization-based self-esteem. Our findings add to the literature by examining how we can anticipate and manage change under an empowering context, building on social exchange and uncertainty reduction theories